EQUITY OR DEBT RESTRUCTURING RESTRUCTURING - Del Carpio Gallegos, Javier (1999)
The paper focuses on one problem that is affecting a number of industrial enterprises, and what alternatives may be companies that have debt problems, and what proposals have been raised to find a satisfactory solution to companies, financial institutions and lending institutions.